2009
DOI: 10.1093/ageing/afp100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic implications of dysphagia in elderly patients with pneumonia

Abstract: oropharyngeal dysphagia is a highly prevalent clinical finding in elderly patients with pneumonia and is an indicator of disease severity in older patients with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
244
1
23

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(284 citation statements)
references
References 26 publications
16
244
1
23
Order By: Relevance
“…Yun Lee ( (Cabre, Serra-Prat, Palomera, Almirall, Pallares, & Calve, 2010;Miura et al, 2007;Morris, 2006;Ney et al, 2009;Rofes et al, 2011; …”
mentioning
confidence: 99%
“…Yun Lee ( (Cabre, Serra-Prat, Palomera, Almirall, Pallares, & Calve, 2010;Miura et al, 2007;Morris, 2006;Ney et al, 2009;Rofes et al, 2011; …”
mentioning
confidence: 99%
“…There are conflicting results on association of OD with gender. Some studies suggest that it is associated with males [20], whereas some other studies suggest that gender is not a risk factor for OD [5].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OD is 15%-23% in community-dwelling elders, 56%-78% in nursing homes and, with widely varying prevalence, 17%-71% in hospitalized patients [2][3][4][5]. Studies have also reported that dysphagia in the older population is associated with malnutrition [6], impaired activities of daily living [7,8], increased rates of respiratory tract infection [8], and higher mortality rates [2].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a incoordenação da deglutição (com favorecimento da aspiração traqueal) é um dos principais fatores responsáveis por pneumonias em idosos 8 . Conseqüentemente estas alterações podem contribuir para o aumento dos índices de morbidade 4,[9][10][11] .…”
Section: Introductionunclassified